The young adult"s perception of religion and formal structures: A postmodern perspective - Hall, Herna (HTS teologiese studies, 2013)
The postmodern era has an impact on different dimensions of the contemporary young adult’s social functioning which incorporates perceptions regarding religion and formal structures. This contemporary young adult refers to an individual between the ages of 18 and 25 years. Therefore the goal of this article was to report on research results regarding the perceptions of young adults on religion and formal structures. Within a mixed methods research approach, the exploratory mixed methods research design was utilised. Qualitative data was collected from 47 young adults by means of focus group interviewing. Quantitative data was collected from 1019 respondents utilising a questionnaire. Both groups were selected through the utilisation of purposive sampling. Qualitative data were analysed through thematic analysis, whilst a range of descriptive and inferential statistical procedures was used to analyse quantitative data. The findings indicated that the postmodern young adult displays a tendency to value conventional religious norms and practices, but the element of choice is of importance, as young adults seem to choose the aspects of religion that suit them. An increased interest in and a need for spirituality or a form of transcendence was found. Guidance by formal structures was favoured, but did not necessarily refer to ‘church’ or religious structures. The results illustrated that the contemporary young adult explores and experiments in terms of identity and lifestyle. Views and values seem to be person-specific and based on emotions and experiences with a tendency towards ‘own authority’ and an emphasis on the self. The rise of individualism which characterises the postmodern era has led to the creation of meaning by drawing on personal resources and on own personal moral beliefs and values.